2019
DOI: 10.1002/nau.24025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pelvic organ prolapse and/or continence surgery on pelvic floor muscle function in women: A systematic review

Abstract: Aims To systematically review the evidence for the effect of pelvic organ prolapse (POP) and/or continence surgery on pelvic floor muscle (PFM) morphometry and function in women, and to investigate whether a relationship exists between PFM measures and clinician‐reported objective pelvic floor outcomes postoperatively. Methods Six electronic databases were searched until March 2018. Studies were included if they examined the effect of POP and/or continence surgery on the PFM in women, and reported pre‐ and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The overall reduction of symptomatic and anatomical POP was expected after surgery, but the improvement in PFM contraction was somewhat surprising and not in line with results from a recently published systematic review, which concluded that there is no clear effect of POP surgery on PFM morphology or function 24 . However, only one of the studies included in this review had pelvic floor function as primary outcome, and the findings of this study are in concordance with our findings 42 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The overall reduction of symptomatic and anatomical POP was expected after surgery, but the improvement in PFM contraction was somewhat surprising and not in line with results from a recently published systematic review, which concluded that there is no clear effect of POP surgery on PFM morphology or function 24 . However, only one of the studies included in this review had pelvic floor function as primary outcome, and the findings of this study are in concordance with our findings 42 .…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, previous publications have focused on perioperative and not preoperative PFMT, and there is a lack of studies evaluating the impact of PFMT on pelvic floor muscle (PFM) contraction assessed by ultrasound. In addition, the possible effect of POP surgery on measures of PFM contraction needs further evaluation, as the existing evidence is unclear 24 .…”
Section: Introductionmentioning
confidence: 99%
“…While the overall reduction in symptoms and anatomical changes of POP were expected after surgery, the improvement in pelvic-floor contraction was somewhat surprising and is not in line with the results of a recently published systematic review. This review concluded that there is no clear effect of POP surgery on pelvic-floor morphology or function [ 38 ], although the studies included in this review were heterogeneous and of low quality. It is also surprising that adding a PFMT protocol to surgical treatment does not produce significant differences in pelvic-floor function.…”
Section: Discussionmentioning
confidence: 99%
“…The analyzed studies are characterized by the heterogeneity of participants and surgical interventions, insufficiency in establishing associations between the strength of postoperative muscle contraction and the change in their morphometry, as well as the low rating of the grade of the evidence used. Thus, further well-designed prospective trials are necessary to assess the impact of urogynecological surgery on pelvic floor muscle efficiency, while PFM PREHAB is needed to improve surgical outcomes [24].…”
Section: Could Surgery Improve Pfm Function?mentioning
confidence: 99%